Environmental Malaysia: History, Sovereignty & Statehood - Ahmad Fauzi Wan Husain, Wan; Maizura Abd Rashid, Intan; Hanie Abu Samah, Irza (International Journal of Psychosocial Rehabilitation, 2020)
Malaysia is a federation that was formed by the 1963 Malaysia Agreement, which now consists of the Federation of Malaya, Sabah, and Sarawak. Prior to the formation of Malaysia, the Federation of Malaya already had a constitution that was institutionalized by the nine Malay rulers (Negeri Sembilan was signed by the Yang di-Pertuan Besar and the ruling chiefs) for kingdoms of them, each with the Queen of England representing two of the Straits Settlements: Penang and Malacca in 1957. Ahead of that, the Federation of Malaya was bound by the Federation of Malaya Agreement 1948.